Implementasi Metode Scrum pada Pengembangan Aplikasi Manajemen Pencegahan dan Penanganan Bullying di Sekolah - Pratama, Eva Argarini; Maryani, Ina; Imaniawan, Fabriyan Fandi Dwi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The increasing bullying is based on several factors, and the factor that can be clearly seen is the post-incident handling or follow-up process from both the victim and the perpetrator. Because it is possible that with the incident experienced by the victim (bullying), the victim will become the perpetrator and the perpetrator without any further good mentoring process will remain the perpetrator at another time and victim. So in preventing or handling this bullying, it cannot only focus on the victim (which often happens also does not dare to report the bullying incident experienced) but must also pay attention to the perpetrator's side. In general and mainly, this application has a feature to receive, process and manage follow-up reporting of bullying incidents, which can be used to manage and provide follow-up related to bullying cases that occur, so that it is expected to break the chain of other bullying by both the perpetrator and the victim. The development of this application uses the scrum method which has several advantages including being more efficient and faster in application development where this method prioritizes cooperation, planning and product quality. Based on the results of testing the program/application, it was found that the functions in the application were running according to the expectations of the application developer.